Evaluation of company information sources and references in the Asian countries on the Internet. - Choong, Chee Yan. (2008)
This study was initiated by the need to find out more about the types of company information generated and placed on the Internet web sites focusing on some of the Asian countries which include: Singapore, China, Thailand, Hong Kong, Japan, India, Korea, Taiwan, Indonesia, Malaysia, Philippines and Asia as a whole. To exploit this vast amount of information that is freely available on the Internet, users need to be informed of the precise web location, quality, coverage and contents of the commercial home pages.